Prenatal and perinatal epidemiology of anxiety disorders - Ståhlberg, Tiia (fi=Turun yliopisto|en=University of Turku|, 2023)
Anxiety disorders are the most common psychiatric disorders among children and adolescents. The aetiology of anxiety disorders is known to be multi-factorial and to include genetic and environmental factors. Prenatal and perinatal factors have been associated with other mental health disorders, but there has been less research on the role they play in anxiety disorders. The aim of this thesis was to comprehensively investigate the associations between prenatal and perinatal factors and child and adolescent anxiety disorders, as well as identifying the treated incidence of anxiety disorders. The first step was to conduct a systematic literature review of the existing literature. The following studies were part of the Finnish Prenatal Study of Anxiety disorders (FIPS-Anx), which is an ongoing nested case-control study. This nationwide birth cohort included 22,388 cases, who were born in 1992 – 2006, and diagnosed with anxiety disorders in 1998 – 2012. Each identified case was matched with four controls. The data were obtained from three national Finnish registers: the Care Register for Health Care, the Finnish Medical Birth Register and the Finnish Population Register Centre. Maternal low socioeconomic status and mother being single at the time of birth increased the odds for offspring anxiety disorders. Preterm birth and poor foetal growth increased the odds for anxiety disorders linearly but comorbid conditions of depressive and neurodevelopmental disorders explained these associations. Birth by caesarean section increased the odds for anxiety disorders. Differences in the associations for specific anxiety disorders were observed. The thesis demonstrates associations between prenatal and perinatal factors and child and adolescent anxiety disorders. However, these associations were impacted by comorbid conditions and possibly some residual confounding factors. The findings support the complex multifactorial aetiology model for anxiety disorders rather than major findings for just prenatal or perinatal factors.

Ahdistuneisuushäiriöiden prenataalinen ja perinataalinen epidemiologia Ahdistuneisuushäiriöt ovat lasten yleisimpiä mielenterveydenhäiriöitä. Ahdistuneisuushäiriöiden etiologian tiedetään olevan monitekijäinen, sekä geeneillä että ympäristötekijöillä on osuutensa. Raskauden ja synnytyksen aikana esiintyviä tekijöitä on yhdistetty joihinkin muihin mielenterveyshäiriöihin, mutta ahdistuneisuushäiriöiden osalta tieto prenataalisten ja perinataalisten tekijöiden osuudesta on ollut vielä vajavaista. Tämän väitöskirjan tavoitteena oli selvittää prenataalisten ja perinataalisten tekijöiden yhteyttä lapsuudessa ja nuoruudessa esiintyviin ahdistuneisuushäiriöihin sekä ahdistuneisuushäiriöiden esiintyvyyttä erikoisairaanhoidossa. Ensimmäinen osatyö oli systemaattinen kirjallisuuskatsaus. Muut osatyöt olivat osa käynnissä olevaa tutkimuskokonaisuutta (the Finnish Prenatal Study of Anxiety disorders, FIPS-Anx), joka tutkii ahdistuneisuushäiriöiden prenataalisia ja perinataalisia riskitekijöitä pesiytetyn tapaus-verrokkiasetelman avulla. Maanlaajuinen syntymäkohortti sisälsi 22,388 vuosina 1992 – 2006 syntynyttä lasta ja nuorta, joilla oli diagnosoitu ahdistuneisuushäiriö vuosina 1998 – 2012, sekä jokaista tapausta kohden neljä verrokkia. Tiedot muuttujista saatiin kolmesta kansallisesta rekisteristä. Äidin matala sosioekonominen asema ja yksinhuoltajuus syntymähetkellä, ennenaikainen syntymä ja pieni syntymäpaino viikkoihin nähden sekä syntymä sektiolla olivat yhteydessä suurentuneeseen ahdistuneisuushäiriöiden todennäköisyyteen. Eroja esiintyi eri ahdistuneisuushäiriöiden alatyyppien välillä. Tämä väitöskirja löysi yhteyksiä prenataalisten ja perinataalisten tekijöiden ja lasten ja nuorten ahdistuneisuushäiriöiden välillä. Osa yhteyksistä selittyi kuitenkin psykiatristen komorbiditeettien avulla ja lisäksi jotkin perinataaliset jäännöstekijät voivat mahdollisesti olla osallisina havaittuihin yhteyksiin. Tutkitut prenataaliset ja perinataaliset tekijät selittänevät vain pienen osan ahdistuneisuushäiriöiden monitekijäisestä etiologiasta.